Numerical Analysis of the Influence of Bolt Set on the Shear Resistance of Jointed Rock Masses - Yan-Ping Wang; Liang-Xiao Xiong (Salehan Institute of Higher Education, 2020)
Bolt reinforcement is a standard reinforcement method for jointed rock masses. However, regarding rock anchoring, the mechanical characteristics of the joint surface, as well as the angle between the bolt and the joint sliding surface, are important factors that affect rock support. Therefore, to understand the influence of a set angle, length, normal load, and other conditions that affect the shear strength of bolt joints, this study uses numerical software to establish the shear sliding model of bolt rock masses and analyzes the influence of the setting conditions of the bolt on the shear strength of a bolt rock mass, which can be done by changing the setting method of the bolt and normal mechanical conditions of the sliding surface. The results show that the shear strength of the anchor joint is not affected after the anchor reaches a certain length. The angle of the anchor strongly influences the shear strength of the anchor joint, and the shear strength curve is V-shaped, where the anchor angle is less than 90°. Moreover, the shear strength curve indicates a downward trend when the anchor angle is greater than 90°, and the shear strength of the anchorage joint increases with the increase of the normal load. Under the same anchor length (4 cm) in the anchor angle and shear strength coordinate system, the shear strength curve of the single anchor is above the shear strength curve of the double anchor, which is exclusively in the local anchor angle section under the condition of a large normal load and a large anchor angle. The shear strength curve of the double anchor is above the shear strength curve of the single anchor.